Complement component 3 protects human bronchial epithelial cells from cigarette smoke-induced oxidative stress and prevents incessant apoptosis - Pei, Yuqiang; Zhang, Jing; Qu, Jingge; Rao, Yafei; Li, Danyang; Gai, Xiaoyan; Chen, Yahong; Liang, Ying; Sun, Yongchang (Frontiers in Immunology, 2022)
The complement component 3 (C3) is a pivotal element of the complement system and plays an important role in innate immunity. A previous study showed that intracellular C3 was upregulated in airway epithelial cells (AECs) from individuals with end-stage chronic obstructive pulmonary disease (COPD). Accumulating evidence has shown that cigarette smoke extract (CSE) induces oxidative stress and apoptosis in AECs. Therefore, we investigated whether C3 modulated cigarette smoke-induced oxidative stress and apoptosis in AECs and participated in the pathogenesis of COPD. We found increased C3 expression, together with increased oxidative stress and apoptosis, in a cigarette smoke-induced mouse model of COPD and in AECs from patients with COPD. Different concentrations of CSEinduced C3 expression in 16HBE cells in vitro. Interestingly, C3 knockdown (KD) exacerbated oxidative stress and apoptosis in 16HBE cells exposed to CSE. Furthermore, C3 exerted its pro-survival effects through JNK inhibition, while exogenous C3 partially rescued CSE-induced cell death and oxidative stress in C3 KD cells. These data indicate that locally produced C3 is an important pro-survival molecule in AECs under cigarette smoke exposure, revealing a potentially novel mechanism in the pathogenesis of COPD.